PENGARUH KOMPOS TANDAN KOSONG KELAPA SAWIT DAN CARA PENGOLAHAN TANAHTERHADAP PERTUMBUHAN DAN PRODUKSI PADI GOGO (Oryza sativa L.) DI ANTARA TANAMAN KELAPA SAWIT BELUM MENGHASILKAN - Josua Dewantara Silalahi; Wawan Wawan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aimed to examine the effect of empty oil palm bunches compost (TKKS compost) and soil tillages on upland rice growth and yield as an intercropon immature oil palm plantation. This research was conducted at Experimental Field of Agriculture Faculty, University of Riau on April to August 2016. This research is factorial experiment 4 x 3 and arrangement with Factorial Completely Randomized Block Design (RBD).The first factor is application of TKKS compost (K) with 4 dosage level (tons/ha), K0 (0), K1 (2.5), K2 (5) and K3 (7.5) and second factor is soil tillages (T) with 3 level, zero tillage, minimum tillage and maximum tillage.Each of treatments combination repeated 3 times, thus obtained 36 experimental units which has five samples. Data were analyzed statistically by analysis of variance (ANOVA).The effect of all treatments combination has knowed by Duncan’s New Multiple Range Test (DNMRT) at5 % level. Parameters measured were maximum number of tillers, productive tillers total, rate of plant growth, root and crown ratio, times of panicles out, grains total per panicle, pithy grain percentage, milled rice per plot, and weight of 1000 grains. The result showed combination of 5 tons/ha TKKS compost with maximum tillage gives the greatest result for upland rice growth and yield include milled rice per plot, it is 679.04 g (1.13 tons/ha) though not differwith combination of 7,5 tons/ha TKKS compost with minimum tillage and or maximum tillage significantly. Keywords :Upland rice, TKKS Compost, Soil Tillage